Shedding Light on Denigration: Its etymology and uses - O'Neil, Kaitlin Anne (Lingua Frankly, 2014)
In this short piece, I offer a brief overview of the etymology of the word denigration, outline its semantic development in the English language, and consider controversial implications of the word in modern usage.